RELATIONS BETWEEN BUKHARA EMIRATE AND OTTOMAN TURKS AT THE BEGINNING OF THE 20TH CENTURY - Ibrohim Rahmonjanov (Social science and innovation, 2024)
This article reflects the relations between the Bukhara Emirate and the Ottoman Turks at the beginning of the 20th century, and analyzes current issues such as economic and social relations and issues of mutual cooperation and the influence of the Young Turks movement